RNAProSAL: A device for rapid and standardized collection of saliva RNA and proteins. (February 2015) - Chiang, Samantha H.; Thomas, Gerald A.; Liao, Wei; Grogan, Tristan; Buck, Robert L.; Fuentes, Laurel; Yakob, Maha; Laughlin, Mary J.; Schafer, Chris; Nazmul-Hossain, Abu; Wei, Fang; Elashoff, David; et al.
The stabilization and processing of salivary transcriptome and proteome biomarkers is a critical challenge due to the ubiquitous nature of nucleases and proteases as well as the inherent instability of these biomarkers. Furthermore, extension of salivary transcriptome and proteome analysis to point-of-care and remote sites requires the availability of self-administered ambient temperature collection and storage tools. To address these challenges, a self-contained whole saliva collection and extraction system, RNAProSAL, has been developed that provides rapid ambient temperature collection along with concurrent processing and stabilization of extracellular RNA (exRNA) and proteins. The system was compared to the University of California, Los Angeles (UCLA) standard clinical collection process (standard operating procedure, SOP). Both systems measured total RNA and protein, and exRNA IL-8, glyceraldehyde 3-phosphate dehydrogenase (GAPDH), β-actin and ribosomal protein S9 (RPS9) by qPCR. Proteome analysis was measured by EIA analysis of interleukin-8 (IL-8), and β-actin, as well as total protein. Over 97% of viable cells were removed by both methods. The system compared favorably to the labor-intensive clinical SOP, which requires low-temperature collection and isolation, yielding samples with similar protein and exRNA recovery and stability.